Integrating Small Modular Reactors and Policy Frameworks for Sustainable Energy Security in Indonesia - Mufatdhal; Imam Supriyadi; Rudy Laksmono (Jurnal Multidisiplin Madani, 2024)
This study evaluates the potential of Small Modular Reactors (SMRs) as a sustainable solution for Indonesia's energy diversification. Amid Indonesia’s rising energy demands and environmental commitments, SMRs-particularly Small Modular Molten Salt Reactors (SM-MSRs)-present an alternative to conventional power sources. SMRs offer advantages like modularity, operational efficiency, and safety, making them suitable for Indonesia’s geographically dispersed landscape. Using a qualitative descriptive approach, this research examines the technical, regulatory, and societal factors influencing SMR integration. Findings reveal that while SMRs show competitive Levelized Cost of Electricity (LCOE) compared to coal, challenges remain, including stringent regulatory requirements, high initial capital costs, and limited public acceptance due to nuclear safety concerns. Policy adjustments, community engagement, and collaboration with established SMR programs globally are suggested to address these issues. Additionally, SMRs’ scalability and compatibility with renewables support Indonesia’s goals for a resilient energy mix, potentially transforming remote energy access. This comprehensive approach underscores the viability of SMRs within Indonesia’s energy transition, contributing to a cleaner, more flexible energy infrastructure